Conducting oral and written language adapted tele-assessments with early elementary-age children with autism spectrum disorder. (November 2022) - Conner, Carlin; Henry, Alyssa R; Solari, Emily J; Zajic, Matthew C
Background and aims: Due to the COVID-19 pandemic, tele-health has gained popularity for both providing services and delivering assessments to children with disabilities. In this manuscript, we discuss the process of collecting standardized oral language, reading, and writing tele-assessment data with early elementary children with autism spectrum disorder (ASD) and offer preliminary findings related to child and parent engagement and technology issues. Methods: The data presented are from pretest assessments during an efficacy study examining the electronic delivery of a listening comprehension intervention for children with ASD. Pretest sessions included a battery of standardized language, reading, and writing assessments, conducted over Zoom. The authors operationalized and developed a behavioral codebook of three overarching behavioral categories (parent involvement, child disengagement, and technology issues). Researchers coded videos offline to record frequencies of indicated behaviors across participants and assessment subtests. Results: Involvement from parents accounted for the highest number of codes. Children showed some disengagement during assessment sessions. Technology issues were minimal. Behavioral categories appeared overall limited but varied across participants and assessments. Conclusions: Parent involvement behaviors made up approximately two-thirds of the coded behaviors. Child disengagement behaviors made up approximately one-fourth of the coded behaviors, and these behaviors occurred more frequently across many different participants (with lower frequencies but greater coverage across children). Technology problems specific to responding to assessment items were relatively uncommon. Implications: Clear guidelines including assessment preparation, modification of directions, and guidelines for parents who remain present are among the implications discussed. We also provide practical implications for continued successful adapted tele-assessments for children with ASD.